Impact of Supply Chain Flexibility and Supplier Development on Supply Chain Effectiveness in Automotive Industry of Pakistan - Quershi, Kafeel Uddin; Siddiqui, Danish Ahmed (ABC Journal of Advanced Research, 2019)
The purpose of this research is to study the significance of supply chain strategies namely supplier development and supply chain flexibility towards supply chain effectiveness in automotive industry of Pakistan. A survey was conducted using self-administered questionnaires to collect data from 300 supply chain professionals working in automotive manufacturing companies of Pakistan. The finding indicates that supplier development and supply chain flexibility have positive and significant impact on supply chain effectiveness in automotive industry of Pakistan. The research will help policy makers and management to integrate strategies and practices related to supplier development and flexibility to improve supply chain effectiveness in order to be competitive in automotive industry of Pakistan.